THE ROLE OF PERSONAL INTEPRETATION AS AN EDUCATIONAL MEDIA FOR VISITORS AT THE SONOBUDOYO MUSEUM - Lolita Meilinda; Uystka Hikmatul Kamiliyah NH (STABN Raden Wijaya Wonogiri, 2026)
Interpretive media are available at the Sonobudoyo Museum, but the inaccurate placement of collection information and directions sometimes make it difficult for visitors to navigate certain areas. The museum's limited space is also a problem, as some rooms produce conflicting sounds, which can interfere with interpretation. Therefore, the purpose of this research is to identify and analyze the role of personal interpretation models as an educational media for visitors at the Sonobudoyo Museum. This research is descriptive qualitative research with data collection techniques through observation, interview, documentation, and literature review. The techniques of selecting informants used purposive sampling with the criteria of visitors to the Sonobudoyo Museum who used the services of a guide. There were 12 visitors of Sonobudoyo Museum who were interviewed in this study. The results of this research indicate that the Sonobudoyo Museum implements personal interpretation by providing around 16 guides. The Museum guides have met 4 indicators of personal interpretation that are enjoyable, relevant, organized, and thematic. The fulfillment of these indicators means that the personal interpretation implemented at the Sonobudoyo Museum plays an important role as an educational media, especially in enhancing visitor’s knowledge and educational experiences.